High-strength anti-cracking building solid waste recycled concrete and preparation method thereof

CN123003226APending Publication Date: 2026-10-30GUANGXI SANWEI RAIL MANUFACTURING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611402393.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

一方面,再生骨料吸水和释水会改变局部水胶比,使混凝土内部收缩变形不均匀;另一方面,旧砂浆、新水泥浆体和骨料之间的弹性模量及变形能力存在差异,干燥收缩或温度变化产生的应力容易集中在界面区域

Benefits of technology

[0024]1、根据再生粗骨料的24h吸水率控制碳化前的含水状态,使骨料孔隙中既保留碳化所需的水分,又留有供二氧化碳扩散的气相通道。真空-常压换气能够排出连通孔隙和微裂纹中的部分空气,使含二氧化碳气体更均匀地进入附着旧砂浆内部,减少仅有骨料表层得到处理的情况。碳化完成后再次降低骨料含水率,为硅溶胶进入孔隙预留空间;平均粒径较小的硅溶胶在负压和恢复常压的压差作用下优先进入细小孔隙及微裂纹,平均粒径较大的硅溶胶则主要沉积在较宽裂纹、孔口和骨料表层。由此形成由内部填充到表层增强的梯度结构,降低再生粗骨料内部的缺陷集中程度,并改善骨料与新水泥浆体之间的界面连续性,从而提高混凝土的抗压强度和承载稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003226A_ABST
    Figure CN123003226A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high-strength anti-cracking building solid waste recycled concrete and preparation method thereof, and it relates to the technical field of recycled concrete.The method includes water content regulation of recycled coarse aggregate, vacuum-normal pressure carbon dioxide-containing gas exchange carbonization and graded silica sol impregnation enhancement;Waste tire rubber particles are treated with alkali washing and coated with meta-kaolin-limestone powder composite powder on the surface;Two lengths of polypropylene fibers are respectively pre-dispersed with fine aggregate;The reinforced aggregate, cementitious material mixture, coated rubber particles and fiber pre-dispersed material are sequentially mixed and stirred, and then molded and cured.The application enhances recycled aggregate through carbonation and gradient silica sol, combines with the surface of rubber particles localized coating and fiber bridging effect, while retaining the energy consumption and anti-cracking ability of rubber particles, compensates for its strength weakening effect, significantly improves the compressive strength, crack resistance and interface stability of recycled concrete, and realizes the high-value collaborative use of building solid waste and waste tires.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of recycled concrete technology, specifically to a high-strength, crack-resistant recycled concrete from building solid waste and its preparation method. Background Technology

[0002] With the continuous expansion of building demolition, renovation, and infrastructure upgrades, the amount of construction solid waste, such as waste concrete, is constantly increasing. Processing waste concrete into recycled aggregates through sorting, crushing, and screening, and then using it to prepare recycled concrete, can reduce the amount of construction solid waste stockpiled and the consumption of natural sand and gravel resources, demonstrating significant resource utilization value.

[0003] Waste concrete suffers varying degrees of damage during service and crushing. The recycled coarse aggregate derived from it typically has a certain amount of old cement mortar adhering to its surface, and may also contain pores and microcracks resulting from crushing. Compared to the more dense structure of natural aggregate, recycled coarse aggregate has a higher water absorption rate and greater strength fluctuations. When preparing concrete, the internal pores of the aggregate affect the distribution of mixing water, and a relatively weak interface transition zone easily forms between the adhering old mortar and the new cement paste. Under load, cracks easily initiate and propagate from these defective areas, thus limiting the compressive strength and long-term load-bearing stability of the recycled concrete.

[0004] Recycled concrete also exhibits a relatively pronounced tendency to crack. On one hand, the water absorption and release of recycled aggregates alters the local water-cement ratio, leading to uneven shrinkage and deformation within the concrete. On the other hand, differences in the elastic modulus and deformation capacity exist between old mortar, new cement paste, and aggregates, causing stresses generated by drying shrinkage or temperature changes to easily concentrate in the interface region. Ordinary cement-based materials have limited tensile deformation capacity; if effective energy dissipation and bridging structures are lacking after microcracks form, the cracks may rapidly propagate, affecting the durability and service life of the component.

[0005] Increasing the density of recycled aggregates improves the load-bearing capacity of concrete, but simply reinforcing the aggregates is insufficient to suppress shrinkage cracks in the cement matrix. Introducing crack-resistant materials with elastic deformation and fiber bridging properties can delay crack propagation, but the modulus of elastic binders is significantly lower than that of cement paste and reinforced recycled aggregates, easily leading to the formation of localized low-stiffness regions around them. When the binder dosage, surface condition, and feeding method are not properly controlled, this mesoscopic stiffness difference can cause stress re-concentration, partially offsetting the strength gain obtained from reinforcing recycled aggregates. Therefore, mechanical reinforcement measures and crack-resistant toughening measures cannot be simply superimposed; coordinated design of the binder interface and the main cementitious structure is also necessary.

[0006] The technical problem to be solved by this invention is how to improve the load-bearing capacity of recycled coarse aggregate and its interface area by adopting a processing method that is readily available, cost-controllable and industrially feasible, under the condition of using a high proportion of recycled aggregate from construction solid waste, while enhancing the concrete's ability to suppress shrinkage cracks and stress cracks; and further reducing the offsetting effect of the local low stiffness interface introduced by elastic colloids on the strength strengthening effect, so that the resulting recycled concrete has both high mechanical strength, crack resistance and performance stability. Summary of the Invention

[0007] The purpose of this invention is to provide a high-strength, crack-resistant recycled concrete from building solid waste and its preparation method, so as to solve the technical problems mentioned in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] A method for preparing high-strength, crack-resistant recycled concrete from building solid waste includes the following steps:

[0010] (1) The 24-hour water absorption rate A24 of the recycled coarse aggregate based on dry weight was determined. The moisture content of the recycled coarse aggregate was adjusted to 55% to 65% of A24. At least two ventilation cycles consisting of vacuuming and introducing carbon dioxide gas to atmospheric pressure were performed in a closed device. Then carbonization was carried out under atmospheric pressure and carbon dioxide atmosphere. The carbonized recycled coarse aggregate was ventilated and dehumidified. The first silica sol was sprayed under negative pressure. After returning to atmospheric pressure, the second silica sol was sprayed and wet curing was carried out to obtain reinforced recycled coarse aggregate. The average particle size of colloidal silica in the first silica sol was smaller than that in the second silica sol.

[0011] (2) The waste tire granules of three particle sizes were mixed, treated with sodium hydroxide aqueous solution, and then washed and dehydrated; two polypropylene fibers of different lengths were premixed with some fine aggregates to obtain two fiber predispersed materials.

[0012] (3) Mix metakaolin and limestone powder to prepare composite cementitious powder. Take a portion of the composite cementitious powder and roll it with the dehydrated waste tire rubber particles to make the composite cementitious powder adhere to the surface of the waste tire rubber particles to obtain powder-coated rubber particles. Dry mix the remaining composite cementitious powder with cement to obtain a cementitious material mixture.

[0013] (4) The reinforced recycled coarse aggregate, the remaining fine aggregate, the cementitious material mixture and a portion of the mixing liquid are mixed, and then the powder-coated granules and the two fiber pre-dispersed materials are added, and then the remaining mixing liquid is added. After stirring, molding and curing, high-strength crack-resistant recycled building solid waste concrete is obtained.

[0014] Preferably, the recycled coarse aggregate from construction solid waste is obtained from waste concrete through sorting, crushing, screening, washing, and drying at a temperature not exceeding 40°C; the particle size of the recycled coarse aggregate from construction solid waste is 5–20 mm, the water absorption rate in 24 hours is not higher than 6%, the crushing index is not higher than 20%, and the mud content is not higher than 1%; after adjusting its moisture content to 55%–65% of A24, it is sealed and balanced for 4–8 hours.

[0015] Preferably, the temperature of the ventilation cycle and carbonization treatment is 15-25℃ and the relative humidity is 55%-65%. Each ventilation cycle includes: evacuating to a gauge pressure of -0.08 to -0.06 MPa and holding for 3 minutes, then introducing a mixed gas with a carbon dioxide volume fraction of 18%-22% to atmospheric pressure and holding for 5 minutes. The ventilation cycle is performed 2-3 times, and then carbonization is carried out in the atmospheric pressure atmosphere formed by the mixed gas for 4-6 hours. The total treatment time of the ventilation cycle and atmospheric pressure carbonization does not exceed 8 hours.

[0016] Preferably, the carbonized recycled coarse aggregate is dehumidified by ventilation at 25–35°C until its moisture content is 25%–35% of A24. Both the first and second silica sols are alkaline silica sols with a pH of 9.0–10.5. The first silica sol has an average particle size of 20–30 nm and a silica mass fraction of 10%. The amount of the first silica sol is 2.5% of the dry weight of the recycled coarse aggregate. It is sprayed twice under a gauge pressure of -0.06 MPa, maintained for 5 minutes after spraying, and then restored to normal pressure within 10 minutes. The second silica sol has an average particle size of 80–120 nm and a silica mass fraction of 20%. The amount of the second silica sol is 1.5% of the dry weight of the recycled coarse aggregate. It is sprayed under normal pressure and continuously rolled for 10 minutes. Then, it is cured for 24–48 hours at 20–25°C and a relative humidity of not less than 95%.

[0017] Preferably, the three particle sizes of waste tire rubber particles are 0.5–1.0 mm, 1.0–2.0 mm, and 2.0–3.0 mm, respectively, with a mass ratio of 30:45:25. The sodium hydroxide aqueous solution has a mass fraction of 4%–6%, the mass ratio of dry rubber particles to sodium hydroxide aqueous solution is 1:3–1:5, the treatment temperature is 20–30°C, the stirring speed is 150–250 r / min, and the treatment time is 30–60 min. The treated waste tire rubber particles are rinsed with water until the pH of the final washing solution is 7.5–8.5 and the pH difference between the final washing solution and the influent is not greater than 0.5. Then, mechanical dehydration is performed to achieve a surface moisture content of 2%–3% based on the mass of dry rubber particles.

[0018] Preferably, the volume of the waste tire rubber granules accounts for 3% to 5% of the total absolute volume of the waste tire rubber granules and fine aggregates; the lengths of the two types of polypropylene fibers are 6 mm and 12 mm, respectively, with the 6 mm long polypropylene fibers accounting for 0.05% to 0.07% of the concrete volume and the 12 mm long polypropylene fibers accounting for 0.03% to 0.05% of the concrete volume, and the total volume fraction of the two types of polypropylene fibers is 0.08% to 0.12%; each type of polypropylene fiber is premixed with 15 to 20 times its mass of dry fine aggregates for 60 seconds.

[0019] Preferably, the median particle size D50 of the metakaolin is 3-8 μm; the mass fraction of calcium carbonate in the limestone powder is not less than 90%, and the median particle size D50 is 8-15 μm; the mass ratio of metakaolin to limestone powder is 1.5:1 to 2.5:1; the composite cementitious powder accounts for 8%-10% of the total mass of the cementitious material, and the total mass of the cementitious material includes the composite cementitious powder adhering to the surface of the waste tire rubber particles; take 6%-8% of the composite cementitious powder equivalent to the dry rubber particles and roll-mix it with the dehydrated waste tire rubber particles for 60-90 seconds and let it stand for 5 minutes, and dry-mix the remaining composite cementitious powder with cement for 60-120 seconds.

[0020] Preferably, each cubic meter of the recycled construction waste concrete comprises 440-470 kg of cementitious material, 1000-1100 kg of reinforced recycled coarse aggregate (based on saturated surface dry weight), and 640-700 kg of fine aggregate, with a water-cement ratio of 0.30-0.34. The cementitious material consists of 90%-92% P·O 52.5 ordinary Portland cement and 8%-10% composite cementitious powder. All coarse aggregate is the reinforced recycled coarse aggregate. The volume of waste tire rubber particles accounts for 3%-5% of the total absolute volume of waste tire rubber particles and fine aggregate. The total volume fraction of the two types of polypropylene fibers is 0.08%-0.12%. The water-reducing agent is a polycarboxylate superplasticizer solution with a solid content of 20%, and its dosage is 1.0%-1.3% of the total mass of the cementitious material.

[0021] Preferably, the amount of added water is determined by deducting the water in the polycarboxylate superplasticizer solution, the surface water carried by the coated granules, and the surface water carried by the fine aggregate from the designed effective water volume. The added water is then mixed with the polycarboxylate superplasticizer solution to form the mixing liquid. The adsorbed water inside the reinforced recycled coarse aggregate in the saturated surface-dry state is not included in the effective water volume. The mixture of reinforced recycled coarse aggregate, fine aggregate not used to prepare fiber predispersed material, and cementitious material is dry-mixed for 60 seconds. 70% of the total amount of mixing liquid is added and stirred for 60-90 seconds. Then, coated granules, predispersed material containing 6 mm long polypropylene fibers, and predispersed material containing 12 mm long polypropylene fibers are added sequentially. The remaining 30% of the mixing liquid is then added and stirred for another 120 seconds. The mixture is poured, compacted, and covered. It is demolded after 24 hours and cured for 28 days at 20±2℃ and a relative humidity of not less than 95%.

[0022] A high-strength, crack-resistant recycled concrete from building solid waste is prepared by the method described above.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] 1. The moisture content of the recycled coarse aggregate before carbonation is controlled based on its 24-hour water absorption rate, ensuring that the aggregate pores retain both the moisture required for carbonation and gaseous channels for carbon dioxide diffusion. Vacuum-atmospheric pressure ventilation removes some air from the interconnected pores and microcracks, allowing carbon dioxide gas to enter the attached old mortar more evenly, reducing the likelihood of only the aggregate surface being treated. After carbonation, the aggregate moisture content is further reduced to allow space for silica sol to enter the pores. Silica sol with smaller average particle size preferentially enters fine pores and microcracks under the pressure difference between negative pressure and restored atmospheric pressure, while silica sol with larger average particle size mainly deposits in wider cracks, pore openings, and the aggregate surface. This creates a gradient structure from internal filling to surface reinforcement, reducing the concentration of defects within the recycled coarse aggregate and improving the interfacial continuity between the aggregate and the new cement paste, thereby increasing the compressive strength and load-bearing stability of the concrete.

[0025] 2. Sodium hydroxide aqueous solution treatment is mainly used to remove oil, zinc soap, and other hydrophobic deposits from the surface of waste tire rubber particles. It also moderately increases the surface roughness and wettability of the particles, enabling them to achieve more stable physical bonding within the cement paste. The three particle sizes are distributed within the paste space of different scales. When the concrete undergoes tensile or shrinkage deformation, they absorb some of the crack propagation energy through elastic deformation, mitigating local stress peaks. 6mm long polypropylene fibers primarily restrain early-formed fine cracks, while 12mm long polypropylene fibers bridge larger crack areas as cracks continue to propagate. Pre-dispersing both types of fibers with fine aggregates reduces fiber entanglement and local agglomeration. This allows the energy dissipation of the particles and the fiber bridging effect to form a mutually reinforcing crack-resistant system within the concrete, thereby delaying crack initiation, propagation, and penetration.

[0026] 3. After carbonization and gradient silica sol treatment, the stiffness and load-bearing capacity of recycled coarse aggregate are improved, while waste tire rubber particles still have a low elastic modulus. When both exist in concrete, local low-stiffness interface zones are easily formed around the rubber particles. This interface zone causes abrupt stiffness changes and stress concentration at the mesoscale, partially offsetting the strength gain obtained by strengthening with recycled coarse aggregate. To address this, this invention combines metakaolin and limestone powder into a single composite cementitious powder, employing a combination of localized coating on the particle surface and dispersed incorporation of the main cementitious material. The smaller particle size and larger specific surface area of ​​metakaolin allow it to penetrate the fine grooves and interparticle spaces on the particle surface, while limestone powder plays a rigid filling and hydration nucleation role at a larger scale, spatially separating the metakaolin particles and reducing local agglomeration of ultrafine metakaolin on the particle surface. The two first form a uniform and continuous mineral powder coating layer through complementary particle sizes. In the cement hydration system, metakaolin provides active silica-alumina components, which is beneficial for increasing the amount of aluminosilicate gel with cementing effect; limestone powder provides a carbonate environment that is conducive to the formation and stabilization of carbonate hydration products, while also providing deposition sites for these products. The two powders do not react directly during the coating process, but rather function separately and synergistically within the cement hydration environment, further filling the pores around the cement particles and increasing the interfacial solid volume. The remaining composite cementitious powder is also dispersed in the main cementitious material, reducing the compositional difference between the cement particle coating layer and the surrounding cement matrix, creating a smoother stiffness transition between the cement particles, cement paste, and reinforced recycled coarse aggregate. This synergistic effect does not change the low modulus of the cement particles themselves, but it reduces interfacial defects and stress concentration around the particles, mitigating the adverse effects of the particles on the compressive strength of concrete. While retaining the energy-dissipating and crack-resistant properties of the cement particles, it effectively compensates for the load-bearing gain obtained from the reinforcement of recycled aggregates. Attached Figure Description

[0027] Figure 1This is a low-magnification SEM image of the high-strength, crack-resistant recycled concrete from building solid waste prepared in Example 1 of the present invention.

[0028] Figure 2 This is a high-magnification SEM image of the high-strength, crack-resistant recycled concrete from building solid waste prepared in Example 1 of the present invention. Detailed Implementation

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] Example 1

[0031] A method for preparing high-strength, crack-resistant recycled concrete from building solid waste includes the following steps:

[0032] 1. Preparation of Enhanced Recycled Coarse Aggregate

[0033] Waste concrete was sorted, crushed, screened, and washed, then dried at 30℃, and 1200.000 kg of oven-dried recycled coarse aggregate was weighed. The aggregate had a particle size of 5–20 mm, a 24-hour water absorption rate (A24) of 5.0%, a crushing index of 18%, and a mud content of 0.6%.

[0034] 33,000 kg of water was evenly sprayed to bring the aggregate moisture content to 2.75%, which is 55% of A24. The mixture was then sealed and balanced for 4 hours. A vacuum was then created in a sealed drum at 15°C and 55% relative humidity, reducing the gauge pressure to -0.06 MPa and maintaining this pressure for 3 minutes. A mixture of 18% carbon dioxide and 82% air was then introduced to atmospheric pressure and maintained for 5 minutes. This ventilation cycle was repeated twice. Finally, the mixture was carbonized at atmospheric pressure for 4 hours under the same mixed atmosphere. The total processing time for ventilation and carbonization was 4 hours and 16 minutes.

[0035] After carbonization, the mixture was ventilated at 25°C until the moisture content reached 1.25%, which is 25% of A24. 30.000 kg of the first silica sol was sprayed twice, 15.000 kg each time, under a gauge pressure of -0.06 MPa. This sol had a silica solid content of 10%, an average colloidal silica particle size of 20 nm, and a pH of 9.0, containing 3.000 kg of silica and 27.000 kg of water. After spraying, the mixture was kept at atmospheric pressure for 5 minutes, and then returned to normal pressure within 10 minutes. Then, 18.000 kg of the second silica sol was sprayed under normal pressure and rolling conditions. This sol had a silica solid content of 20%, an average colloidal silica particle size of 80 nm, and a pH of 9.0, containing 3.600 kg of silica and 14.400 kg of water. Rolling was continued for 10 minutes, and the mixture was cured for 24 hours at 20°C and 95% relative humidity, then adjusted to a saturated surface-dry state.

[0036] 2. Preparation of colloids, fibers and composite cementitious powders

[0037] Based on apparent density 2650 kg / m³ 3 Fine aggregate and apparent density 1100 kg / m³ 3 Waste tire rubber pellets were measured using 8.987 kg of dry-basis waste tire rubber pellets, ensuring that the pellet volume accounted for 3.0% of the total absolute volume of the rubber pellets and fine aggregates. This included 2.696 kg of pellets with a diameter of 0.5–1.0 mm, 4.044 kg of pellets with a diameter of 1.0–2.0 mm, and 2.247 kg of pellets with a diameter of 2.0–3.0 mm.

[0038] 1.078 kg of sodium hydroxide and 25.883 kg of water were used to prepare a 26.961 kg sodium hydroxide aqueous solution with a concentration of 4.0%, making the mass ratio of dry colloidal particles to alkaline solution 1:3. The solution was treated at 20℃ and 150 r / min for 30 min. The particles were then rinsed five times with 90.000 kg of water at an influent pH of 7.2, with the pH of the final rinse solution controlled at 7.5. Mechanical dehydration was performed until the surface water content of the colloidal particles was 2.0%, and the particles carried 0.180 kg of surface water.

[0039] 21.120 kg of metakaolin with a D50 of 3 μm was mixed with 14.080 kg of limestone powder with a calcium carbonate content of 90% and a D50 of 8 μm to obtain 35.200 kg of composite cementitious powder, with a mass ratio of 1.5:1. 0.539 kg of the composite cementitious powder was mixed with dehydrated cementitious particles by rolling for 60 s and allowed to stand for 5 min. The remaining 34.661 kg of composite cementitious powder was then dry-mixed with 404.800 kg of P·O 52.5 ordinary Portland cement for 60 s.

[0040] 0.455 kg of 6 mm long polypropylene fiber was premixed with 6.825 kg of saturated surface-dry fine aggregate for 60 s; 0.273 kg of 12 mm long polypropylene fiber was premixed with 4.095 kg of saturated surface-dry fine aggregate for 60 s. The volume fractions of the two fibers were 0.05% and 0.03%, respectively.

[0041] 3. Concrete mix design

[0042] Per cubic meter of concrete:

[0043] 404.800 kg P·O 52.5 ordinary Portland cement;

[0044] 21.120 kg metakaolin;

[0045] 14.080 kg limestone powder;

[0046] 1100,000 kg of saturated, dry, reinforced recycled coarse aggregate;

[0047] 700,000 kg of saturated dry fine aggregate;

[0048] 8.987 kg of dry-based waste tire rubber pellets;

[0049] 0.455kg, 6mm long polypropylene fiber;

[0050] 0.273kg, 12mm long polypropylene fiber;

[0051] 4.400 kg of polycarboxylate superplasticizer solution with a solid content of 20%;

[0052] 128.300kg of water added.

[0053] 440.000 kg of cementitious material corresponds to a water-cement ratio of 0.30, with an effective water consumption of 132.000 kg. 4.400 kg of polycarboxylate superplasticizer solution contains 3.520 kg of water, the dehydrated cementitious particles carry 0.180 kg of surface water, and the fine aggregate has zero surface water; therefore, the required additional water is 128.300 kg. Mixing 128.300 kg of additional water with 4.400 kg of polycarboxylate superplasticizer solution yields 132.700 kg of mixing liquid.

[0054] Mix 1100,000 kg of reinforced recycled coarse aggregate, 689,080 kg of fine aggregate not used for fiber predispersion, and 439,461 kg of cementitious material by dry mixing for 60 seconds. Add 92,890 kg of mixing liquid and stir for 60 seconds. Then add the coated granules and the two types of fiber predispersed materials in sequence, followed by 39,810 kg of mixing liquid, and continue stirring for 120 seconds. Pour, vibrate, and cover the mixture. Demold after 24 hours and cure for 28 days at 18°C ​​and 95% relative humidity.

[0055] Example 2

[0056] A method for preparing high-strength, crack-resistant recycled concrete from building solid waste includes the following steps:

[0057] 1. Preparation of Enhanced Recycled Coarse Aggregate

[0058] Waste concrete was sorted, crushed, screened, and washed, then dried at 35℃, and 1200.000 kg of oven-dried recycled coarse aggregate was weighed. The aggregate had a particle size of 5–20 mm, a 24-hour water absorption rate (A24) of 5.5%, a crushing index of 19%, and a mud content of 0.8%.

[0059] 39.600 kg of water was evenly sprayed to bring the aggregate moisture content to 3.30%, which is 60% of A24. The mixture was then sealed and balanced for 6 hours. A vacuum was then created in a sealed drum at 20°C and 60% relative humidity until the gauge pressure reached -0.07 MPa and was maintained for 3 minutes. A mixture of 20% carbon dioxide and 80% air was then introduced until atmospheric pressure was reached and maintained for 5 minutes. This ventilation cycle was repeated three times. Finally, the mixture was carbonized at atmospheric pressure for 5 hours, for a total treatment time of 5 hours and 24 minutes.

[0060] After carbonization, the mixture was ventilated at 30℃ until the moisture content reached 1.65%, which is 30% of A24. Then, 30.000 kg of the first silica sol was sprayed twice, 15.000 kg each time, under a gauge pressure of -0.06 MPa. This sol had a silica solid content of 10%, an average colloidal silica particle size of 25 nm, and a pH of 9.8, containing 3.000 kg of silica and 27.000 kg of water. After spraying, the mixture was kept at atmospheric pressure for 5 minutes, and then returned to normal pressure within 10 minutes. Then, 18.000 kg of the second silica sol was sprayed. This sol had a silica solid content of 20%, an average colloidal silica particle size of 100 nm, and a pH of 9.8, containing 3.600 kg of silica and 14.400 kg of water. The mixture was rolled for another 10 minutes and cured at 22℃ and 97% relative humidity for 36 hours, then adjusted to a saturated surface-dry state.

[0061] 2. Preparation of colloids, fibers and composite cementitious powders

[0062] 11.502 kg of dry-based waste tire rubber pellets were used, so that the volume of the rubber pellets accounted for 4.0% of the total absolute volume of the rubber pellets and fine aggregates. This included 3.450 kg of rubber pellets with a particle size of 0.5–1.0 mm, 5.176 kg of rubber pellets with a particle size of 1.0–2.0 mm, and 2.876 kg of rubber pellets with a particle size of 2.0–3.0 mm.

[0063] 2.300 kg of sodium hydroxide and 43.706 kg of water were used to prepare a 46.006 kg solution of 5.0% sodium hydroxide, making the mass ratio of dry colloidal particles to alkaline solution 1:4. The solution was treated at 25℃ and 200 rpm for 45 min. The particles were then rinsed six times with 120.000 kg of water at an influent pH of 7.5, with the final rinse solution pH controlled at 8.0. Mechanical dehydration was performed until the surface water content of the colloidal particles was 2.5%, and the particles carried 0.288 kg of surface water.

[0064] 27.000 kg of metakaolin with a D50 of 5.5 μm was mixed with 13.500 kg of limestone powder with a calcium carbonate content of 95% and a D50 of 11.5 μm to obtain 40.500 kg of composite cementitious powder, with a mass ratio of 2:1. 0.805 kg of the composite cementitious powder was mixed with dehydrated cementitious particles by rolling for 75 s and allowed to stand for 5 min. The remaining 39.695 kg of composite cementitious powder was then dry-mixed with 409.500 kg of P·O52.5 ordinary Portland cement for 90 s.

[0065] 0.546 kg of 6 mm long polypropylene fiber was premixed with 9.828 kg of saturated surface-dry fine aggregate for 60 s; 0.364 kg of 12 mm long polypropylene fiber was premixed with 6.552 kg of saturated surface-dry fine aggregate for 60 s. The volume fractions of the two types of fiber were 0.06% and 0.04%, respectively.

[0066] 3. Concrete mix design

[0067] Per cubic meter of concrete:

[0068] 409.500 kg P·O 52.5 ordinary Portland cement;

[0069] 27,000 kg metakaolin;

[0070] 13,500 kg limestone powder;

[0071] 1045.000 kg saturated surface-dried reinforced recycled coarse aggregate;

[0072] 665,000 kg of saturated dry fine aggregate;

[0073] 11.502 kg of dry-based waste tire rubber pellets;

[0074] 0.546kg, 6mm long polypropylene fiber;

[0075] 0.364kg, 12mm long polypropylene fiber;

[0076] 5.400 kg of polycarboxylate superplasticizer solution with a solid content of 20%;

[0077] 139.392 kg of water added.

[0078] 450.000 kg of cementitious material corresponds to a water-cement ratio of 0.32, with an effective water consumption of 144.000 kg. 5.400 kg of polycarboxylate superplasticizer solution contains 4.320 kg of water, the dehydrated cementitious particles carry 0.288 kg of surface water, and the fine aggregate has zero surface water; therefore, the required additional water is 139.392 kg. Mixing 139.392 kg of additional water with 5.400 kg of polycarboxylate superplasticizer solution yields 144.792 kg of mixing liquid.

[0079] Mix 1045.000 kg of reinforced recycled coarse aggregate, 648.620 kg of fine aggregate not used for fiber predispersion, and 449.195 kg of cementitious material by dry mixing for 60 seconds. Add 101.354 kg of mixing liquid and stir for 75 seconds. Then add the coated granules and the two types of fiber predispersed materials in sequence, followed by 43.438 kg of mixing liquid, and continue stirring for 120 seconds. Pour, vibrate, and cover the mixture. Demold after 24 hours and cure for 28 days at 20℃ and 97% relative humidity.

[0080] Example 3

[0081] A method for preparing high-strength, crack-resistant recycled concrete from building solid waste includes the following steps:

[0082] 1. Preparation of Enhanced Recycled Coarse Aggregate

[0083] Waste concrete was sorted, crushed, screened, and washed, then dried at 40℃, and 1200.000 kg of oven-dried recycled coarse aggregate was weighed. The aggregate had a particle size of 5–20 mm, a 24-hour water absorption rate (A24) of 6.0%, a crushing index of 20%, and a mud content of 1.0%.

[0084] 46.800 kg of water was evenly sprayed to bring the aggregate moisture content to 3.90%, which is 65% of A24. The mixture was then sealed and balanced for 8 hours. A vacuum was then created in a sealed drum at 25°C and 65% relative humidity, reducing the gauge pressure to -0.08 MPa and maintaining this pressure for 3 minutes. A mixture of 22% carbon dioxide and 78% air was then introduced to atmospheric pressure and maintained for 5 minutes. This ventilation cycle was repeated three times, followed by atmospheric pressure carbonization for 6 hours, for a total treatment time of 6 hours and 24 minutes.

[0085] After carbonization, the mixture was ventilated at 35℃ until the moisture content reached 2.10%, which is 35% of A24. 30.000 kg of the first silica sol was sprayed twice, 15.000 kg each time, under a gauge pressure of -0.06 MPa. This sol had a silica solid content of 10%, an average colloidal silica particle size of 30 nm, and a pH of 10.5, containing 3.000 kg of silica and 27.000 kg of water. After spraying, the mixture was kept at atmospheric pressure for 5 minutes, and then returned to normal pressure within 10 minutes. Then, 18.000 kg of the second silica sol was sprayed. This sol had a silica solid content of 20%, an average colloidal silica particle size of 120 nm, and a pH of 10.5, containing 3.600 kg of silica and 14.400 kg of water. The mixture was rolled for another 10 minutes and cured for 48 hours at 25℃ and 98% relative humidity, then adjusted to a saturated surface-dry state.

[0086] 2. Preparation of colloids, fibers and composite cementitious powders

[0087] 13.982 kg of dry-based waste tire rubber pellets were used, so that the volume of the rubber pellets accounted for 5.0% of the total absolute volume of the rubber pellets and fine aggregates. This included 4.195 kg of rubber pellets with a particle size of 0.5–1.0 mm, 6.292 kg of rubber pellets with a particle size of 1.0–2.0 mm, and 3.495 kg of rubber pellets with a particle size of 2.0–3.0 mm.

[0088] 4.195 kg of sodium hydroxide and 65.715 kg of water were used to prepare a 69.910 kg sodium hydroxide aqueous solution with a concentration of 6.0%, making the mass ratio of dry colloidal particles to alkaline solution 1:5. The solution was treated at 30℃ and 250 r / min for 60 min. The particles were then rinsed seven times with 140.000 kg of water at an influent pH of 8.0, with the pH of the final rinse solution controlled at 8.5. Mechanical dehydration was performed until the surface water content of the colloidal particles was 3.0%, and the particles carried 0.419 kg of surface water.

[0089] 33.571 kg of metakaolin with a D50 of 8 μm was mixed with 13.429 kg of limestone powder with a calcium carbonate content of 98% and a D50 of 15 μm to obtain 47.000 kg of composite cementitious powder, with a mass ratio of 2.5:1. 1.119 kg of the composite cementitious powder was mixed with dehydrated granules by rolling for 90 s and allowed to stand for 5 min. The remaining 45.881 kg of composite cementitious powder was then dry-mixed with 423.000 kg of P·O 52.5 ordinary Portland cement for 120 s.

[0090] 0.637 kg of 6 mm long polypropylene fiber was premixed with 12.740 kg of saturated surface-dry fine aggregate for 60 s; 0.455 kg of 12 mm long polypropylene fiber was premixed with 9.100 kg of saturated surface-dry fine aggregate for 60 s. The volume fractions of the two fibers were 0.07% and 0.05%, respectively.

[0091] 3. Concrete mix design

[0092] Per cubic meter of concrete:

[0093] 423.000 kg P·O 52.5 ordinary Portland cement;

[0094] 33.571 kg metakaolin;

[0095] 13.429 kg limestone powder;

[0096] 1000,000 kg of saturated, dry, reinforced recycled coarse aggregate;

[0097] 640,000 kg of saturated dry fine aggregate;

[0098] 13.982 kg of dry-based waste tire rubber granules;

[0099] 0.637kg polypropylene fiber, 6mm in length;

[0100] 0.455kg, 12mm long polypropylene fiber;

[0101] 6.110 kg of polycarboxylate superplasticizer solution with a solid content of 20%;

[0102] 154.493 kg of water added.

[0103] 470,000 kg of cementitious material corresponds to a water-cement ratio of 0.34, with an effective water consumption of 159.800 kg. 6.110 kg of polycarboxylate superplasticizer solution contains 4.888 kg of water, the dehydrated cementitious particles carry 0.419 kg of surface water, and the fine aggregate has zero surface water; therefore, the required additional water is 154.493 kg. Mixing 154.493 kg of additional water with 6.110 kg of polycarboxylate superplasticizer solution yields 160.603 kg of mixing liquid.

[0104] Mix 1000.000 kg of reinforced recycled coarse aggregate, 618.160 kg of fine aggregate not used for fiber predispersion, and 468.881 kg of cementitious material by dry mixing for 60 seconds. Add 112.422 kg of mixing liquid and stir for 90 seconds. Then add the coated granules and the two types of fiber predispersed materials in sequence, followed by 48.181 kg of mixing liquid, and continue stirring for 120 seconds. Pour, vibrate, and cover the mixture. Demold after 24 hours and cure for 28 days at 22℃ and 98% relative humidity.

[0105] Comparative Example 1: Based on Example 1, 1100.000 kg of reinforced recycled coarse aggregate was replaced by saturated surface-dry recycled coarse aggregate that had not been carbonized and treated with silica sol. All other raw materials, dosages, preparation steps and curing conditions were the same as in Example 1.

[0106] Comparative Example 2: Based on Example 1, the recycled coarse aggregate was carbonized with carbon dioxide only according to the conditions of Example 1. After carbonization, the first and second silica sols were not sprayed. All other conditions were the same as in Example 1.

[0107] Comparative Example 3: Based on Example 1, 30.000 kg of the first silica sol and 18.000 kg of the second silica sol were premixed and sprayed onto carbonized recycled coarse aggregate at normal pressure in one go. Small-particle-size silica sol negative pressure infiltration and large-particle-size silica sol normal pressure deposition were not performed. All other conditions were the same as in Example 1.

[0108] Comparative Example 4: Based on Example 1, 8.987 kg of dry waste tire rubber particles were not treated with sodium hydroxide aqueous solution, but were washed with 90.000 kg of water and dehydrated to a surface moisture content of 2.0%. All other conditions were the same as in Example 1.

[0109] Comparative Example 5: Based on Example 1, without adding 8.987 kg of dry-based waste tire rubber particles, and using 21.650 kg of saturated surface-dry fine aggregate of equal volume to make up the volume occupied by the rubber particles, all other conditions are the same as in Example 1.

[0110] Comparative Example 6: Based on Example 1, 0.455 kg of 6 mm long polypropylene fiber and 0.273 kg of 12 mm long polypropylene fiber were replaced with 0.728 kg of 6 mm long polypropylene fiber, so that the total volume fraction of polypropylene fiber was kept at 0.08%, and all other conditions were the same as in Example 1.

[0111] Comparative Example 7: Based on Example 1, 21.120 kg metakaolin and 14.080 kg limestone powder were not added. Instead, 440.000 kg of P·O 52.5 ordinary Portland cement was used as all cementing materials, and the powder coating treatment on the surface of the cement particles was cancelled. All other conditions were the same as in Example 1.

[0112] Comparative Example 8: Based on Example 1, 35.200 kg of composite cementitious powder formed from 21.120 kg of metakaolin and 14.080 kg of limestone powder was dry-mixed with 404.800 kg of P·O 52.5 ordinary Portland cement. 0.539 kg of composite cementitious powder was not removed to coat the cement particles. All other conditions were the same as in Example 1.

[0113] Comparative Example 9: Based on Example 1, instead of adding 14.080 kg of limestone powder, 14.080 kg of P·O 52.5 ordinary Portland cement was used to make up the mass, and 0.539 kg of 21.120 kg of metakaolin was used to coat the granules. All other conditions were the same as in Example 1.

[0114] Comparative Example 10: Based on Example 1, instead of adding 21.120 kg of metakaolin, 21.120 kg of P·O52.5 ordinary Portland cement was used to make up the mass, and 0.539 kg of limestone powder was taken from 14.080 kg of limestone powder to coat the granules. All other conditions were the same as in Example 1.

[0115] Performance testing

[0116] 1. Slump

[0117] The slump of the concrete mixture was determined according to GB / T 50080—2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". After wetting and fixing the slump cone and base plate, a representative mixture from the same batch was placed into the cone in three layers, each layer filling approximately one-third of the cone's volume. The mixture was then tamped evenly with a tamping rod 25 times. After leveling the top surface, the slump cone was steadily lifted vertically within 3–7 seconds. The entire process from loading to lifting the cone should not exceed 150 seconds. When the specimen stopped slumping or reached 30 seconds, the height difference between the cone height and the highest point of the specimen was measured, accurate to 1 mm, and rounded to 5 mm. Three independent batches were tested for each mix proportion. The values ​​listed in the table are the arithmetic mean of the three batch results, rounded to 5 mm.

[0118] 2. Cube compressive strength

[0119] The 28-day cubic compressive strength was determined according to GB / T 50081—2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". Three 150mm×150mm×150mm cubic specimens were molded for each mix proportion. After molding, the specimens were covered and allowed to stand for 24 hours before demolding. They were then placed in a standard curing room at (20±2)℃ and a relative humidity of not less than 95% for 28 days. After wiping off surface moisture and inspecting the pressure surface, the specimens were placed in the center of a compression testing machine and continuously and uniformly loaded at a stress rate of 0.8MPa / s until failure. The compressive strength was calculated based on the failure load and the bearing area. The result was taken as the arithmetic mean of the three specimens; if a single value deviated from the median value by more than 15%, it was discarded according to the standard provisions.

[0120] 3. Splitting tensile strength

[0121] The 28-day splitting tensile strength was determined according to GB / T 50081—2019. For each mix design, three 150mm×150mm×150mm cubic specimens were used. After standard curing for 28 days, center lines were marked on the two opposite compression surfaces. A spacer strip was placed along the loading center line, centering the specimen. A stress rate of 0.08 MPa / s was continuously applied until splitting failure. The splitting tensile strength was calculated based on the maximum load, specimen side length, and stress area. The result was taken as the arithmetic mean of the three specimens; outliers were handled according to the provisions of this standard.

[0122] 4. Flexural strength

[0123] The 28-day flexural strength was determined according to the three-point loading method of GB / T 50081—2019. Three 150mm×150mm×600mm prism specimens were molded for each mix proportion and cured under standard conditions for 28 days. The test span was set to 450mm. The specimens were adjusted so that the molded side was the tension surface. Symmetrical loading was applied using two equidistant loading points at a stress rate of 0.08MPa / s until failure. The maximum load was recorded, and the flexural strength was calculated using the standard formula. Results were valid when the failure surface was located between the two loading points, and the group value was determined as the arithmetic mean of the three valid specimens.

[0124] 5. Static compressive modulus of elasticity

[0125] The 28-day static compressive modulus of elasticity was determined according to GB / T 50081—2019. Six 150mm×150mm×300mm prism specimens were prepared for each mix design and cured to 28 days. Three specimens were used to determine the axial compressive strength, and the other three were used for the elastic modulus test. Deformation measuring devices with a gauge length of 150mm were installed on opposite sides of the specimens. Three pre-compression cycles were performed at a stress rate of 0.6MPa / s, with a lower limit stress of 0.5MPa and an upper limit stress of one-third of the axial compressive strength of the same group. The secant modulus of elasticity was calculated by taking the average strain difference corresponding to the upper and lower limit stresses in the third cycle. The group value was taken as the arithmetic mean of the three specimens.

[0126] 6. Drying shrinkage

[0127] 90-day drying shrinkage was determined according to the contact method in GB / T 50082—2024 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete". Three 100mm×100mm×515mm prism specimens were molded for each mix proportion, with probes installed at both ends. From the time of water addition and mixing until 3 days after curing, the probes were cleaned and the initial length was measured. The specimens were then placed in a constant temperature and humidity chamber with a temperature of (20±2)℃, relative humidity of (60±5)%, and good air circulation. A horizontal shrinkage meter with an effective gauge length of 540mm and a reading accuracy of 0.001mm was used. The length changes were measured at 1, 3, 7, 14, 28, 45, 60, and 90 days after the initial reading, and the shrinkage rate was calculated based on the effective gauge length. The 90-day drying shrinkage referred to in this test is the shrinkage rate calculated from the initial reading on day 3, and the result is the arithmetic mean of the three specimens.

[0128] 7. Early cracking

[0129] Early cracking within 24 hours was determined according to the plate method in GB / T 50082—2024. Two 800mm×600mm×100mm plate specimens were molded for each mix proportion, with seven parallel crack inducers arranged inside the mold. After molding and finishing, the specimens were placed in a test environment with a temperature of (20±2)℃ and a relative humidity of (60±5)%. After 30 minutes of molding, a parallel airflow of (5.0±0.2) m / s was provided by an air source positioned 100mm above the center of the specimen. The test time was calculated from the start of concrete mixing until (24±0.5) hours. The length of each crack was measured with a steel ruler, and the maximum width was measured with a crack width gauge with a graduation of 0.01mm and a magnification of not less than 40x. The total cracked area per unit area was calculated by dividing the sum of the products of each crack length and the maximum width by the effective tested area of ​​the specimen, and the arithmetic mean of the two specimens was taken.

[0130] 8. Chloride ion migration coefficient

[0131] The 28-day unsteady-state chloride ion migration coefficient was determined according to the RCM method in GB / T 50082—2024. Three cylindrical specimens with a diameter of (100±1) mm and a height of (50±2) mm were prepared for each formulation and cured to standard for 28 days. The specimens were then placed under vacuum at an absolute pressure of 1–5 kPa for 3 hours, followed by the injection of saturated calcium hydroxide solution under vacuum for another 1 hour. After restoring to normal pressure, the specimens were immersed for (18±2) hours. The experimental environment temperature was maintained at 20–25℃. The anolyte solution was 0.3 mol / L sodium hydroxide solution, and the cathode solution was 10% sodium chloride solution. A voltage of (30±0.2) V was initially applied, and the formal voltage and energizing time were adjusted according to the standard based on the initial current. After energizing, the specimens were split axially, and 0.1 mol / L silver nitrate solution was sprayed onto the fresh cross-section. After approximately 15 minutes of color development, the chloride ion penetration depth was measured at 10 equidistant points. The DRCM was calculated using the standard formula, and the arithmetic mean of the three specimens was taken.

[0132] Table 1:

[0133] Example 1 175 61.8 4.96 7.42 34.8 480 125 7.1 Example 2 185 61.0 5.12 7.66 33.5 493 101 7.3 Example 3 200 58.9 5.25 7.81 31.6 511 81 7.7 Comparative Example 1 165 51.7 4.26 6.41 29.8 572 204 11.0 Comparative Example 2 170 56.6 4.51 6.74 31.8 538 179 9.1 Comparative Example 3 175 58.7 4.70 7.00 33.0 515 155 8.0 Comparative Example 4 180 58.4 4.62 6.92 33.5 489 142 7.9 Comparative Example 5 185 66.0 5.12 7.58 37.3 438 152 6.8 Comparative Example 6 180 61.3 4.78 7.10 34.7 485 149 7.2 Comparative Example 7 190 55.0 4.40 6.65 32.0 522 145 10.2 Comparative Example 8 175 58.0 4.65 7.00 33.1 505 134 8.4 Comparative Example 9 165 59.0 4.75 7.12 33.9 510 139 6.9 Comparative Example 10 195 56.3 4.55 6.82 32.9 465 148 9.4

[0134] As can be seen from the data in the table:

[0135] The 28-day compressive strengths of Comparative Examples 1, 2, 3, and 1 were 51.7 MPa, 56.6 MPa, 58.7 MPa, and 61.8 MPa, respectively, and the chloride ion migration coefficients were 11.0 × 10⁻⁶, respectively. -12 m 2 / s, 9.1×10 -12 m 2 / s, 8.0×10 -12 m 2 / s and 7.1×10 -12 m2 / s. Compared to untreated aggregates, controlled carbonation can improve the weak structure of old mortar; further, by adopting graded silica sol treatment with small-diameter negative pressure infiltration followed by large-diameter surface deposition, internal pores and surface cracks can be improved simultaneously, thereby enhancing the continuity of force transmission between recycled aggregates and new mortar.

[0136] In Comparative Example 5, after removing the granules, the compressive strength and elastic modulus reached 66.0 MPa and 37.3 GPa, respectively, both higher than those of Example 1. However, the total crack area per unit area after 24 hours decreased from 125 mm². 2 / m 2 Increased to 152mm 2 / m 2 This indicates that while the introduction of adhesive particles reduces local stiffness, it can mitigate early constraint stress through elastic deformation and energy dissipation. Comparative Example 6, using only 6mm fibers while maintaining the same total fiber volume fraction, exhibited weaker splitting tensile strength, flexural strength, and cracking indices than Example 1, demonstrating a complementary scale between the dispersing effect of 6mm fibers on early microcracks and the bridging effect of 12mm fibers on larger cracks. Comparative Example 4, without alkali washing, showed inferior compressive strength, crack area, and chloride ion migration coefficient compared to Example 1, indicating that surface cleanliness and wetting of the adhesive particles are crucial conditions for stable interfacial bonding.

[0137] Comparative Example 7, without either of the two powders, has a compressive strength of 55.0 MPa and a chloride ion migration coefficient of 10.2 × 10⁻⁶. -12 m 2 / s; Comparative Example 8, using the same total amount of composite powder but without particle localization coating, had corresponding indicators of 58.0 MPa and 8.4 × 10⁻⁶ MPa. -12 m 2 / s, still lower than 61.8 MPa and 7.1 × 10 in Example 1. -12 m 2 / s. The fine-particle filling and subsequent active reaction of metakaolin are beneficial for refining the pores of the slurry and the interfacial transition zone, while limestone powder provides filling and nucleation sites, and promotes the stable distribution of hydration products through the combination of carbonate phase and aluminum-containing hydration phase. A small amount of composite powder is preferentially attached to the surface of the colloidal particles, with the remainder dispersed in the main cementitious material, allowing the above effects to be concentrated and covering the periphery of the colloidal particles while also ensuring matrix densification. Comparative Example 9, containing only metakaolin, has a lower chloride ion migration coefficient, but a lower slump and increased drying shrinkage; Comparative Example 10, containing only limestone powder, has better slump and drying shrinkage, but insufficient strength and chloride ion migration resistance. Using Comparative Example 7 as the powder-free baseline, the compressive strength increment of the compound system is 61.8 - 59.0 - 56.3 + 55.0 = 1.5 MPa, indicating that the strength contributions of the two powders in this formulation are not simply additive. The compound system achieves a more balanced workability, mechanical properties, crack resistance, and chloride ion migration resistance.

[0138] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing high-strength, crack-resistant recycled concrete from building solid waste, characterized in that, Includes the following steps: (1) The 24-hour water absorption rate A24 of the recycled coarse aggregate based on dry weight was determined. The moisture content of the recycled coarse aggregate was adjusted to 55% to 65% of A24. At least two ventilation cycles consisting of vacuuming and introducing carbon dioxide gas to atmospheric pressure were performed in a closed device. Then carbonization was carried out under atmospheric pressure and carbon dioxide atmosphere. The carbonized recycled coarse aggregate was ventilated and dehumidified. The first silica sol was sprayed under negative pressure. After returning to atmospheric pressure, the second silica sol was sprayed and wet curing was carried out to obtain reinforced recycled coarse aggregate. The average particle size of colloidal silica in the first silica sol was smaller than that in the second silica sol. (2) The waste tire granules of three particle sizes were mixed, treated with sodium hydroxide aqueous solution, and then washed and dehydrated; two polypropylene fibers of different lengths were premixed with some fine aggregates to obtain two fiber predispersed materials. (3) Mix metakaolin and limestone powder to prepare composite cementitious powder. Take a portion of the composite cementitious powder and roll it with the dehydrated waste tire rubber particles to make the composite cementitious powder adhere to the surface of the waste tire rubber particles to obtain powder-coated rubber particles. Dry mix the remaining composite cementitious powder with cement to obtain a cementitious material mixture. (4) The reinforced recycled coarse aggregate, the remaining fine aggregate, the cementitious material mixture and a portion of the mixing liquid are mixed, and then the powder-coated granules and the two fiber pre-dispersed materials are added, and then the remaining mixing liquid is added. After stirring, molding and curing, high-strength crack-resistant recycled building solid waste concrete is obtained.

2. The preparation method according to claim 1, characterized in that, The recycled coarse aggregate from construction solid waste is obtained from waste concrete through sorting, crushing, screening, washing, and drying at a temperature not exceeding 40°C. The particle size of the recycled coarse aggregate from construction solid waste is 5–20 mm, the water absorption rate in 24 hours is not higher than 6%, the crushing index is not higher than 20%, and the mud content is not higher than 1%. After adjusting its moisture content to 55%–65% of A24, it is sealed and balanced for 4–8 hours.

3. The preparation method according to claim 2, characterized in that, The temperature of the ventilation cycle and carbonization treatment is 15-25℃ and the relative humidity is 55%-65%. Each ventilation cycle includes: evacuating to a gauge pressure of -0.08 to -0.06 MPa and holding for 3 minutes, then introducing a mixed gas with a carbon dioxide volume fraction of 18%-22% to atmospheric pressure and holding for 5 minutes. The ventilation cycle is performed 2-3 times, and then carbonization is carried out in the atmospheric pressure atmosphere formed by the mixed gas for 4-6 hours. The total treatment time of ventilation cycle and atmospheric pressure carbonization does not exceed 8 hours.

4. The preparation method according to claim 3, characterized in that, The carbonized recycled coarse aggregate was dehumidified by ventilation at 25–35°C until its moisture content was 25%–35% of A24. Both the first and second silica sols were alkaline silica sols with a pH of 9.0–10.

5. The first silica sol had an average particle size of 20–30 nm and a silica mass fraction of 10%. The amount of the first silica sol was 2.5% of the dry weight of the recycled coarse aggregate. It was sprayed twice under a gauge pressure of -0.06 MPa, maintained for 5 minutes after spraying, and then returned to normal pressure within 10 minutes. The second silica sol had an average particle size of 80–120 nm and a silica mass fraction of 20%. The amount of the second silica sol was 1.5% of the dry weight of the recycled coarse aggregate. It was sprayed under normal pressure and continued to roll for 10 minutes. Then it was cured for 24–48 hours at 20–25°C and a relative humidity of not less than 95%.

5. The preparation method according to claim 1, characterized in that, The three particle sizes of waste tire rubber particles are 0.5–1.0 mm, 1.0–2.0 mm, and 2.0–3.0 mm, respectively, with a mass ratio of 30:45:

25. The sodium hydroxide aqueous solution has a mass fraction of 4%–6%, and the mass ratio of dry rubber particles to sodium hydroxide aqueous solution is 1:3–1:

5. The treatment temperature is 20–30°C, the stirring speed is 150–250 r / min, and the treatment time is 30–60 min. The treated waste tire rubber particles are rinsed with water until the pH of the final washing solution is 7.5–8.5 and the pH difference between the final washing solution and the influent is no greater than 0.

5. Then, mechanical dehydration is performed to achieve a surface moisture content of 2%–3% based on the mass of dry rubber particles.

6. The preparation method according to claim 5, characterized in that, The volume of the waste tire rubber granules accounts for 3% to 5% of the total absolute volume of the waste tire rubber granules and fine aggregates; the lengths of the two types of polypropylene fibers are 6 mm and 12 mm, respectively, with the 6 mm long polypropylene fibers accounting for 0.05% to 0.07% of the concrete volume and the 12 mm long polypropylene fibers accounting for 0.03% to 0.05% of the concrete volume, and the total volume fraction of the two types of polypropylene fibers is 0.08% to 0.12%; each type of polypropylene fiber is premixed with 15 to 20 times its mass of dry fine aggregates for 60 seconds.

7. The preparation method according to claim 1, characterized in that, The median particle size D50 of the metakaolin is 3-8 μm; the mass fraction of calcium carbonate in the limestone powder is not less than 90%, and the median particle size D50 is 8-15 μm; the mass ratio of metakaolin to limestone powder is 1.5:1 to 2.5:1; the composite cementitious powder accounts for 8%-10% of the total mass of the cementitious material, and the total mass of the cementitious material includes the composite cementitious powder adhering to the surface of the waste tire rubber particles; take 6%-8% of the composite cementitious powder equivalent to the dry rubber particles and roll and mix it with the dehydrated waste tire rubber particles for 60-90 seconds and let it stand for 5 minutes, and dry mix the remaining composite cementitious powder with cement for 60-120 seconds.

8. The preparation method according to claim 7, characterized in that, Each cubic meter of the recycled construction waste concrete comprises 440-470 kg of cementitious material, 1000-1100 kg of reinforced recycled coarse aggregate (based on saturated surface dry weight), and 640-700 kg of fine aggregate, with a water-cement ratio of 0.30-0.

34. The cementitious material consists of 90%-92% P·O 52.5 ordinary Portland cement and 8%-10% composite cementitious powder. All coarse aggregate is the reinforced recycled coarse aggregate. The volume of waste tire rubber particles accounts for 3%-5% of the total absolute volume of waste tire rubber particles and fine aggregate. The total volume fraction of the two types of polypropylene fibers is 0.08%-0.12%. The water-reducing agent is a polycarboxylate water-reducing agent solution with a solid content of 20%, and its dosage is 1.0%-1.3% of the total mass of the cementitious material.

9. The preparation method according to claim 8, characterized in that, The amount of added water is determined by deducting the water in the polycarboxylate superplasticizer solution, the surface water carried by the coated granules, and the surface water carried by the fine aggregate from the designed effective water volume. The added water is then mixed with the polycarboxylate superplasticizer solution to form the mixing liquid. The adsorbed water inside the reinforced recycled coarse aggregate in the saturated surface-dry state is not included in the effective water volume. The mixture of reinforced recycled coarse aggregate, fine aggregate not used to prepare fiber predispersed material, and cementitious material is dry-mixed for 60 seconds. 70% of the total amount of mixing liquid is added and stirred for 60-90 seconds. Then, coated granules, predispersed material containing 6 mm long polypropylene fibers, and predispersed material containing 12 mm long polypropylene fibers are added sequentially. The remaining 30% of the mixing liquid is then added and stirred for another 120 seconds. The mixture is poured, compacted, and covered. It is demolded after 24 hours and cured for 28 days at 20±2℃ and a relative humidity of not less than 95%.

10. A high-strength, crack-resistant recycled concrete from building solid waste, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.